Music Training Enhances Rapid Neural Plasticity of N1 and P2 Source Activation for Unattended Sounds - Seppänen, Miia; Hämäläinen, Jarmo; Pesonen, Anu-Katriina; Tervaniemi, Mari (Frontiers in Human Neuroscience, 2012)
Neurocognitive studies demonstrate that long-term musical training enhances the processing of unattended sounds. It is not clear, however, whether musical training modulates also rapid (within tens of minutes) neural plasticity for sound encoding. To study this, we examined whether adult musicians display enhanced rapid neural plasticity when compared to nonmusicians. More specifically, we examined the modulation of P1, N1, and P2 responses to regular standard sounds in an oddball paradigm between unattended passive blocks which were separated by an active task. Source analysis for event-related potentials showed that N1 and P2 source activation decreased selectively in musicians already after fifteen minutes of passive exposure to sounds and that P2 source activation re-enhanced after the active task in musicians. Additionally, event-related potential (ERP) analysis revealed that in both musicians and nonmusicians, P2 ERP amplitude enhanced after fifteen minutes of passive exposure but only at frontal electrodes. Furthermore, in musicians, N1 ERP enhanced after the active discrimination task but only at parietal electrodes. Musical training modulates the rapid plasticity reflected in N1 and P2 source activation for unattended regular standard sounds. Enhanced rapid plasticity of N1 and P2 might reflect the faster auditory perceptual learning in musicians when compared to nonmusicians.